(untitled) (Papeles, 2022)
This research is a reflection on the interfaces of the rights of Nature that have become a new decolonial paradigm in the face of the ecological crisis derived from the current model of exploitation of natural resources for the production and reproduction of capitalism in the modern-colonial world-system. The problem is whether the possible opening of doors to a new era that brings a symbolic dimension of the judicialization of rights to Nature would not only be of nominal legality. The general objective is to demonstrate the feasibility of recognizing Nature as a subject because it is a manifestation of the Pluricultural State and to emphasize that biocentric conceptions are capable of promoting more effective legal protection of damages caused against Nature, as well as as it takes the form of a step against the coloniality exercised by the countries of the North on the global South. To carry out the research, a critical,methodological line and the methodology of literature review were adopted to present a theoretical observation on the debate on the subject in Latin America with the emergence of the New Latin American Constitutionalism, especially in the 21st century, as a manifestation of biocultural rights.